Satellite interferometry for high-precision detection of ground deformation at a carbon dioxide storage site. (November 2015) - Samsonov, Sergey; Czarnogorska, Magdalena; White, Don
Abstract : Highlights: Introduced Aquistore Carbon Capture and Storage project in Saskatchewan, Canada. Described methodology for monitoring ground deformation with MSBAS-InSAR. Produced two-dimensional deformation rate maps of background processes. Modeled ground deformation due to elastic and poroelastic sources. Suggested prototype that can be used for monitoring deformation at other CCS sites. Abstract: At the Aquistore CCS site, located in the southeastern Saskatchewan, Canada, carbon dioxide (CO2 ) is to be injected at variable rates of up to 1500 tonne/day. The storage reservoir consists of a dominantly clastic, brine-filled interval (Deadwood and Winnipeg formations) which reside at 3150–3350 m depth. Ground deformation at this site is being monitored to track pressure-induced uplift and potential upward migration of CO2 through faults and fractures. Deformation monitoring is conducted using space-borne Differential Interferometric Synthetic Aperture Radar (DInSAR), capable of achieving millimeter precision and meter spatial resolution over the entire monitored area. During June 2012–October 2014, prior to CO2 injection, two ascending and two descending high-resolution RADARSAT-2 data sets were acquired and simultaneously processed with the advanced Multidimensional Small Baseline (MSBAS) DInSAR producing vertical and horizontal East-West deformation time series with six days temporal sampling, four times more frequent than the repeat cycle of each individual data set. Two years of monitoring prior to the onset of (CO2 ) injection allowed measurement of the deformation field of the background natural and anthropogenic processes. Vertical and horizontal ground deformation was detected with the rates of ±1.0 and ±0.5 cm/year and with precision of 0.3 and 0.2 cm/year (2 σ ) correspondingly. Background motion (shape and magnitude) may resemble deformation signals due to potential upward migration of CO2 through faults and fractures. Analytic elastic and poroelastic modeling was performed to estimate the ground deformation that will be produced when injection begins. For this purpose, rock properties determined from geophysical well logs and in situ temperature and pressure were used. For the elastic model it was determined that a maximum of vertical deformation of 1.6 cm/year will be located around the injection well, whereas the maximum of horizontal deformation of 0.6 cm/year will be located about 3 km away from the injection well. For a more realistic poroelastic model, it was determined that maximum vertical deformation will not exceed 1.6 cm and maximum horizontal deformation will not exceed 0.1 cm/year during the entire 25 year injection cycle. According to this model, the established monitoring network cannot detect predicted horizontal motion since it is below its sensitivity, whereas for detection of vertical motion ground-based monitoring sites need to be installed near and also at distance from the injection well. Six day temporal sampling allows determination of the transient uplift phase. A proposed MSBAS strategy overcomes limitations of the classical DInSAR, such as sparse temporal resolution and the lack of ability to extract individual deformation components from the line-of-sight retrievals, and can be implemented at other onshore CCS sites for operational monitoring, using readily available SAR data.